Service diversification and supply chain integration strategies in optimizing the sea toll and pioneer shipping programs - Berlianto, Wawan Rudi; Iryani, Novi; Pangesti Lestari, Surya Murni; Pahala, Indra; Handaru, Agung Wahyu (Jurnal Mantik, 2025)
Indonesia, as the world's largest archipelagic state, faces chronic logistical challenges, particularly in the frontier, Remote, Disadvantaged, and Border Areas . The purpose of this study is to investigate how service diversification and vertical-horizontal integration strategies can be applied to optimize Indonesia’s maritime logistics programs. Government-initiated programs such as the Sea Toll and Pioneer Shipping aim to reduce regional disparities by subsidizing maritime logistics. However, the effectiveness of these programs is undermined by systemic fragmentation, low return cargo rates, and weak institutional coordination. This literature review evaluates strategic approaches based on service diversification and supply chain integration, drawing from theoretical frameworks including Ansoff’s Matrix, Porter’s Value Chain, Institutional Theory, and the Resource-Based View. By synthesizing recent international studies, this article presents a comprehensive strategy to enhance program impact and support inclusive, efficient maritime connectivity in Indonesia. The findings highlight the importance of integrating digital logistics systems, expanding multimodal service access (such as LCL and reefer logistics), and aligning institutional coordination across stakeholders. These strategies reduce cost disparities and strengthen logistics performance in underserved maritime regions